OPTIMIZING CROSSFLOW TURBINE BLADES FOR POWER ENHANCEMENT AT PICO HYDRO POWER PLANT (PLTPH) USING ANSYS FLUENT - Yosi Apriani; Herlinda Herlinda; Zulkiffli saleh; Wiwin Oktaviani Anwar; Ian Mochamad Sofian (Jurusan Pendidikan Teknik Elektro, 2024)
Renewable energy has become an important solution in dealing with the problem of climate change and resource scarcity. This study aims to analyze the effect of variations in the number of Crossflow turbine blades on output power at the Pico Hydro Power Plant (PLTPH). PLTPH is a water-based power plant with less than 5 kW of power, ideal for remote areas. Simulations were performed using SolidWorks software for turbine geometry design, Computational Fluid Dynamics (CFD), and ANSYS Fluent for fluid flow simulation. The simulation results show that the number of spoons and the speed of the water flow have a significant impact on the power produced. The optimal configuration is found on a 20-blade turbine that produces a maximum power of 4,695 Watts at a flow rate of 6 m/s. These findings can guide the efficient design of Crossflow turbines for PLTPH applications in remote areas.